Effect of Proprioceptive Neuromuscular Facilitation Technique Combined with Kinesio Taping on Upper Limb Motor Function of Patients with Stroke - XU Xuedi; ZHAO Kai; CHEN Yan; ZHANG Akang; GAO Xiaoping; CHEN Hemu (康复学报)
ObjectiveTo observe the effect of proprioceptive neuromuscular facilitation (PNF) technique combined with kinesio taping on upper limb motor function of patients with stroke.MethodsA total of 67 stroke patients hospitalized in the department of rehabilitation medicine of the First Affiliated Hospital of Anhui Medical University from January 2021 to January 2022 were randomly divided into control group, PNF group and combined group, with 22, 22, 23 cases in each group. During the course of the treatment, 2, 2 and 3 cases dropped out or discontinued respectively. Finally, there were 20 cases included in each group. The control group received conventional physical modality therapy (20 min a time, twice a day, six times a week), comprehensive training of hemiplegic limbs (40 min a time, once a day, five times a week) and occupational therapy (20 min a time, once a day, five days a week), lasting for four weeks. The PNF group received upper limb PNF training on the basis of the control group, including 20 min comprehensive training of hemiplegic limbs and 20 min PNF training, once a day, five times a week, lasting for four weeks. The combined group received kinesio taping on the basis of the PNF group, and the taping was changed once every three days, lasting for four weeks. Before treatment and after treatment for four weeks, Fugl-Meyer motor assessment scale (FMA) was used to evaluate the upper limb motor function; modified Ashworth scale (MAS) was used to evaluate the muscle tone; surface electromyography (sEMG) was used to evaluate integrated electromyography (iEMG) and co-contraction ratio (CR).Results(1) Upper limb motor function: Compared with that before treatment, FMA scores of the PNF group and the combined group increased significantly after treatment, and the differences were statistically significant (P<0.05). Compared with the control group, FMA scores of the PNF group and the combined group were significantly higher after treatment, and the differences were statistically significant (P<0.05). Compared with the PNF group, FMA score of the combined group was significantly higher after treatment, and the difference was statistically significant (P<0.05). (2) Muscle tone of upper limb: Compared with that before treatment, there was no significant difference in MAS score of all the three groups after treatment (P>0.05); there was no significant difference in MAS score in the PNF group and the combined group with the control group after treatment (P>0.05). (3) Surface electromyography: compared with that before treatment, CR in the control group decreased significantly after treatment (P<0.05), the iEMG value and CR in the PNF group and the combined group decreased significantly after treatment (P<0.05). Compared with the control group, the CR of the PNF group was significantly lower after treatment (P<0.05), the iEMG value and CR in the combined group were significantly lower after treatment, and the differences were statistically significant (P<0.05). Compared with the PNF group, the iEMG value of the combined group was significantly lower, and the difference was statistically significant (P<0.05).ConclusionPNF technique combined with kinesio taping can effectively improve the upper limb motor function and upper limb EMG signal conduction in patients with stroke, which is recommended for clinical application.